The creation of feedback in training as a mobilizing factor for the cognitive activity of students - Jabbarov, Rashid (2020)
The article examines the relationship between cognitive activity and creation of feedback in learning. The study was conducted on 120 students of Baku State University. Experimental and control groups were selected in the research and carried out in two stages. During the research, modern teaching methods and other techniques were used to increase cognitive activity. A comparative analysis of the first and second stages showed that the relationship between increased cognitive activity and the feedback mechanism is bilateral. That is, the creation of feedback increases cognitive activity, increasing cognitive activity inevitably creates a feedback mechanism. The research has shown that there is a correlation between learning achievements (r = 0.29), self-realization (r = 0.33), self-assessment (r = 0.25), learning motivation (r = 0.35) and cognitive activity in the experimental group. The study concludes that high academic performance is associated with the desire to achieve the highest results, develop potential and increase self-esteem through academic achievement. The study concludes that the desire to develop the potential, to achieve the highest results with high academic performance and to increase self-esteem through academic achievement are interconnected. It is the feedback mechanism that can act as a condition for enhancing learning achievements.